2020
DOI: 10.1002/gps.5293
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to depressive symptoms and self‐reported diagnosis of depression in community‐dwelling older Chileans: A national cross‐sectional analysis

Abstract: AimThe aims of this study were to describe the prevalence of screening‐positive depression and to identify the frequency and factors related to self‐reported depression diagnosis in people with screen‐positive depression.MethodsUsing the Geriatric Depression Scale (GDS‐15), 4065 older Chileans were screened for depression. Social and health variables were included. Self‐reported depression diagnosis and antidepressant use were analyzed according to screen‐positive depression (GDS‐15 ≥ 5). Chi‐square and logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 33 publications
4
19
0
2
Order By: Relevance
“…Men with a positive screen for any level of depression were less likely to self-report a medical diagnosis, as previously found by Aravena et al [ 23 ]. As these authors had reported, we observed associations between age, educational attainment, and the odds of diagnosis, but we found that older women were less likely to self-report a depression diagnosis, and that educational attainment increased this likelihood only among men.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Men with a positive screen for any level of depression were less likely to self-report a medical diagnosis, as previously found by Aravena et al [ 23 ]. As these authors had reported, we observed associations between age, educational attainment, and the odds of diagnosis, but we found that older women were less likely to self-report a depression diagnosis, and that educational attainment increased this likelihood only among men.…”
Section: Discussionsupporting
confidence: 73%
“…Our results contribute to the previous information about depressive disorders among older adults in Chile. Aravena et al [ 23 ] found a prevalence of positive screen for MDD of 6.9% in this group in 2009, assessed with the 15-item Geriatric Depression Scale (GDS-15). Our study found a higher prevalence (9.4%), which could be attributed to the use of a different screening test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations